Enhanced propagation of motile bacteria on surfaces due to forward scattering - Stanislaw Makarchuk (Nature Portfolio, 2019)
Microorganisms tend to live in heterogeneous environments. Here the authors investigate the influence of this heterogeneity on bacteria swimming near a surface in the presence of obstacles; these are found to enhance the cells’ propagation rather than hinder it for an optimal obstacle density.